2017
DOI: 10.1103/physrevb.96.024427
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain stability of parametric synchronization in a spin-torque nano-oscillator based on a magnetic tunnel junction

Abstract: We report on time-domain stability of the parametric synchronization in a spin-torque nanooscillator (STNO) based on a magnetic tunnel junction. Time-domain measurements of the instantaneous frequency (fi) of a parametrically synchronized STNO show random short-term unlocking of the STNO signal for low injected radio-frequency (RF) power, which cannot be revealed in time-averaged frequency domain measurements. Macrospin simulations reproduce the experimental results and reveal that the random unlocking during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Figure e shows the simulated phase noise ( S ϕ ) for mixed-phase (black line) and β-phase Ta (red line) at the threshold condition. Both the plots show the typical 1/ f 2 phase noise behavior. , It is found that the β-phase Ta system shows a much higher phase noise compared to mixed-phase Ta. This also leads to higher linewidth for the β-phase Ta system as shown in the inset of Figure e.…”
Section: Resultsmentioning
confidence: 81%
“…Figure e shows the simulated phase noise ( S ϕ ) for mixed-phase (black line) and β-phase Ta (red line) at the threshold condition. Both the plots show the typical 1/ f 2 phase noise behavior. , It is found that the β-phase Ta system shows a much higher phase noise compared to mixed-phase Ta. This also leads to higher linewidth for the β-phase Ta system as shown in the inset of Figure e.…”
Section: Resultsmentioning
confidence: 81%
“…The phase noise in both series and parallel configurations shows a typical 1/ f 2 behavior of STOs due to the thermal fluctuations and π-phase slips, which indicates a partial phase locking. The linewidth can be reduced to the source linewidth by injection or sub-harmonic locking as seen in vortex STOs 44 if 1/ f 2 phase noise is completely suppressed 25 , 45 . The main reason for this limitation is a higher phase noise in uniformly magnetized STOs which might require a much higher rf power for the complete phase noise suppression 25 , 45 .…”
Section: Resultsmentioning
confidence: 99%
“…The linewidth can be reduced to the source linewidth by injection or sub-harmonic locking as seen in vortex STOs 44 if 1/ f 2 phase noise is completely suppressed 25 , 45 . The main reason for this limitation is a higher phase noise in uniformly magnetized STOs which might require a much higher rf power for the complete phase noise suppression 25 , 45 . For the series configuration in Fig.…”
Section: Resultsmentioning
confidence: 99%